THE RELATIONSHIP OF SELF-CONTROL WITH ONLINE GAME ADDICTION AMONG TEENAGERS IN KENAGARIAN TAEH BUKIK - Muttaqin alan said; Magistarina, Elrisfa (Causalita, 2024)
Online game addiction can have a bad impact on teenagers. Online game addiction in teenagers is influenced by self-control, when an individual's self-control is low then online game addiction will be high and vice versa. Individuals who are addicted to online games find it difficult to prevent, set time limits for playing online games, and regulate the intensity of playing online games. Online game addiction can have a bad impact on teenagers. This research aims to determine self-control with online game addiction among teenagers in Kenagarian Taeh Bukik. The method used is quantitative with a correlational quantitative design. The research subjects were 60 teenagers who played online games, with a sampling technique using total sampling. Data collection uses an online game addiction scale and a self-control scale. The results of product moment correlation data analysis were r=-0.315 and p=0.014. This shows that there is a negative and significant relationship between online game addiction and self-control in teenagers in Kenagarian Taeh Bukik which can be interpreted as Ha being accepted.